2006
DOI: 10.1007/s10006-006-0688-y
|View full text |Cite
|
Sign up to set email alerts
|

Gesichtsschädelaugmentationen mit porösen Polyethylenimplantaten (Medpor®)

Abstract: Porous polyethylene implants showed a good fibrovascular integration without encapsulation under the light microscope. Giant cells were detected on the surface of the implants. Besides this there was evidence for resorption of the implant material. Fixation with titanium screws is very effective. No implant dislocation or implant fracture occurred. The implants showed high volume stability and were easily handled and contoured. It is not possible to visualize Medpor implants with current imaging techniques, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…PPE implants are available for numerous applications ranging from orbital floor reconstruction [ 2 ] over auricular reconstruction [ 3 ] to facial contour implants [ 4 ]. This implant material has proofed to be biocompatible, long-term stable, non-soluble, and non-resorbable over a period of more than 30 years of clinical use [ 5 7 ]. However, there are applications which are less favorable for implant integration, such as rhinoplasty and reconstructive nose surgery [ 8 ] as well as reconstructions in irradiated or scar tissue, where blood supply is weak [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…PPE implants are available for numerous applications ranging from orbital floor reconstruction [ 2 ] over auricular reconstruction [ 3 ] to facial contour implants [ 4 ]. This implant material has proofed to be biocompatible, long-term stable, non-soluble, and non-resorbable over a period of more than 30 years of clinical use [ 5 7 ]. However, there are applications which are less favorable for implant integration, such as rhinoplasty and reconstructive nose surgery [ 8 ] as well as reconstructions in irradiated or scar tissue, where blood supply is weak [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Use of Medpor implants for areas like the ear, nose and maxilla in syndromic patients is associated with a higher risk of implant failure 39 . A study by Gosau et al 41 showed fibrovascular integration without encapsulation under light microscopy for the Medpor implant. They detected giant cells on the surface of the implants and evidence of implant material resorption.…”
Section: Discussionmentioning
confidence: 97%
“…It has pores of 150–250 µm, a size suitable for the immigration of autologous connective tissue cells, it can be formed intraoperative to a moderate extent [23], [58] and is not relevantly resorbed. However, foreign body giant cells are found histologically in the surroundings which contain the material, so at least minimal degradation must be assumed [60]. It is encased by a connective tissue membrane: encasing and cell immigration thus contribute to stabilization of the implant, in supplement to the titanium screws with which it is customarily affixed [60].…”
Section: Hard Tissue Replacementmentioning
confidence: 99%
“…However, foreign body giant cells are found histologically in the surroundings which contain the material, so at least minimal degradation must be assumed [60]. It is encased by a connective tissue membrane: encasing and cell immigration thus contribute to stabilization of the implant, in supplement to the titanium screws with which it is customarily affixed [60]. Due to the limited formability and limited shock stability, this material is only suitable for smaller defects, since it cannot compete in the same category with individually preformed implants and the possibility they offer with respect to contouring and shock resistance.…”
Section: Hard Tissue Replacementmentioning
confidence: 99%
See 1 more Smart Citation